2016
DOI: 10.4172/2161-1149.1000201
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TLR2 and TLR4 on CD14 Monocytes in Female SLE Patients E

Abstract: Background: Systemic Lupus Erythematous (SLE) is a prototype autoimmune disease of multifactorial origin mainly assigned to defects in the adaptive immune system. However, evidences supported the crucial role of the innate immune system in its pathogenesis. Toll-like receptors (TLRs) have been proposed as important pathways in disease development. This relatively new idea holds promise for new therapeutic strategies. The aim of this work is to measure surface expression of TLR2 and TLR4 on CD14+ monocytes in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Further studies have shown that this negative control of TLR4 surface expression not only appears in microbial infections but may also be a universal mechanism triggered in response to increased inflammation of various etiologies. Reduced expression of TLR4 on peripheral monocytes was observed in autoimmunology diseases, acute pancreatitis, or chronic kidney diseases [56][57][58][59][60]. Krejsek et al [61] observed TLR4 downregulation on monocytes of patients undergoing coronary artery bypass grafting, an invasive procedure associated with activating an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have shown that this negative control of TLR4 surface expression not only appears in microbial infections but may also be a universal mechanism triggered in response to increased inflammation of various etiologies. Reduced expression of TLR4 on peripheral monocytes was observed in autoimmunology diseases, acute pancreatitis, or chronic kidney diseases [56][57][58][59][60]. Krejsek et al [61] observed TLR4 downregulation on monocytes of patients undergoing coronary artery bypass grafting, an invasive procedure associated with activating an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have shown that this negative control of TLR4 surface expression not only appears in microbial infections but may also be a universal mechanism triggered in response to increased inflammation of various etiologies. Reduced expression of TLR4 on peripheral monocytes was observed in autoimmunology diseases, acute pancreatitis, or chronic kidney diseases [56–60]. Krejsek et al .…”
Section: Discussionmentioning
confidence: 99%